Reflections of Brecht’s Political Theatre on African Drama: Imbuga’s Successor and Rotimi’s If… in Perspective - Mwai, Wangari; Mugubi, John; Tengya, Pomak Frank (Nairobi Journal of Humanities and Social Sciences, 2022)
This paper takes a critical look at the influences of Bertolt Brecht’s dramaturgy on the works of African playwrights. It is evident that the theoretical approach and style of Bertolt Brecht has shaped the new narratives that has been unleashed on the modern stage. His devoted treatise on social theatre theory and the creation of storylines that are centred on around the emancipation of the people has served as a template for most playwrights in developing countries. This article looks at the deployment of the Brechtian Theatre model by two prolific African playwrights. Francis Imbuga’s Successor and Ola Rotimi’s If… from the popular nature of the storylines that captures the historicity that shapes the African political landscape, to the everyman characterization that the playwrights deploy; this nature of characterization easily speaks to the African because it propagates its historical and immediate challenges. All these attributes are firmly entrenched in Bertolt Brecht’s Theatre. The article looks at the historical nature of the plays and their social relevance to the development of man in the modern society.